2012
DOI: 10.1097/mpa.0b013e31821fc90c
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of Human Pancreatic β Cells for Cytomegalovirus Infection and the Effects on Cellular Immunogenicity

Abstract: In vivo β-cell HCMV infection and infection-enhanced cellular immunogenicity may have important consequences for native or transplanted β-cell survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 61 publications
2
28
0
Order By: Relevance
“…This correlation was confirmed by Smelt et al (2012), who showed that CMV can infect human b-cells, inducing the expression of inflammatory factors and cytokines.…”
Section: Cytomegalovirussupporting
confidence: 57%
“…This correlation was confirmed by Smelt et al (2012), who showed that CMV can infect human b-cells, inducing the expression of inflammatory factors and cytokines.…”
Section: Cytomegalovirussupporting
confidence: 57%
“…The fact that CMV DNA can be detected in samples of pancreatic tissue from patients with T2D strongly supports the association of CMV with T2D (Lohr and Oldstone 1990). Human pancreatic β-cells have also been shown to be susceptible to in vitro infection with CMV (Smelt et al 2012).…”
Section: And Type 2 Diabetesmentioning
confidence: 60%
“…Several viruses have been linked to T1DM, i.e Coxsackie, Mumps, Rubella, Cytomegalovirus, Retroviruses and Rotaviruses [136][137][138][139], otherwise several evidences link enteroviruses, in particular Coxsackie B4 virus to T1DM [140].…”
Section: Viruses and β-Cellsmentioning
confidence: 99%